(untitled) (Research, Society and Development, 2024)
Introduction: Breastfeeding plays a crucial role in maternal and child health, providing benefits for both babies and mothers. Despite this, difficulties in breastfeeding are faced due to socioeconomic factors, lack of support and inadequate information. Good breastfeeding not only strengthens the bond between mother and baby, but also contributes to physical, immunological and cognitive development. Objective: to verify whether the newborn’s degree of breastfeeding difficulty directly affects the score of the validated LATCH instrument. Methodology: Quantitative and observational study carried out in a hospital unit, sample of newborns in the Maternal and Child Ward during August to December 2022 with inclusion criteria that included full-term newborns, without complications to perform the breastfeeding assessment using the LATCH score and questionnaire with mothers. Results and Discussion: Of the 89 newborns, 7 were excluded. The results showed that 72 babies with breastfeeding difficulties had a significantly lower LATCH score compared to those without difficulties. There was no significant correlation between breastfeeding difficulties and individual LATCH components. Conclusion: Although there is no direct correlation between specific breastfeeding difficulties and individual LATCH components, the overall mean LATCH score was significantly lower in babies with difficulties. This highlights the importance of early assessment and intervention to ensure successful breastfeeding and strengthen the bond between mothers and newborns.